THEORETICAL-HISTORICAL ANALYSIS OF JURY TRIALS FORMATION IN RUSSIA - I. V. Yermakova (Russian Journal of Economics and Law)
Since the recognition of the need to restore justice by a jury Concept of Judicial Reform in the RSFSR (1991), and so far in the society, environment and practitioners there is no unique relationship to this institution. Current problems in the establishment and functioning of the jury, as well as its criticism is largely the same as occurred in the XIX - early XX centuries. In this paper the author attempts to briefly review the main stages of the jurors' institute in Russia. The study has revealed ​​a number of findings of doctrinal and practical problems.